Menaxhimi i riskut në raste katastrofash – sigurimi i pronave në Kosovë - Myhybije Zallqi Zhara; Ibish Mazreku (Micro, Macro & Mezzo Geoinformation, 2014)
New risks and disaster are the most vulnerable aspects of increasing levels of risk. For several years, many OECD countries are faced with the reappearance of risks, scale and frequency of which would be difficult to imagine before, including modern terrorism, especially that of 11 September 2001, and several natural disasters with their serious consequences. The terms "Risk Society" or the "Society fear", increasingly used to reflect a perception among people close to increasing their exposure to major risks, such as those disasters. Despite their exposure to the risk of serious accidents caused by the impact of natural risks, including earthquakes, floods, fires, droughts and landslides, the frequency and extent of the damage which is likely to increase as a result of climate change, management the risk of natural disasters is very weak in Kosovo and in the region of Western Balkans. Especially in these countries is really nonexistent property coverage homeowners and small businesses by providing disaster. This paper focuses on new policies on disaster risk management, describing the most effective methods of disaster risk management and how to apply them in terms of a small developing economy like Kosovo's economy. Analysis of the level of security in case of natural disasters and other catastrophes, one factor in Kosovo are the main pillars of the paper.